The effect of thermocycling and debonding time on the shear bond strength of different orthodontic brackets bonded with light-emitting diode adhesive (In vitro study) - Harraa S Mohammed-Salih (College of Dentistry/ University of Baghdad, 2014)
Background: Thermocycling simulates the temperature dynamics in the oral environment. This in vitro study done to measure and compare the effect of thermocycling on the shear bond strength of stainless steel and sapphire brackets bonded to human enamel teeth using light cured orthodontic adhesive and debonded at various time, and to measure adhesive remnant index after debonding. Materials and Methods: one-hundred-twenty extracted upper first premolars for orthodontic reason were used in this study; depending on weather thermocycled or not, the sample was divided into two main groups, then within each group 30 teeth were used for stainless-steel brackets (Bionic) and for sapphire brackets (Pure). Both groups were subdivided into three groups (n = 10) according to the debond times: I: debond after 24 hour, II: debond after 7 days and III: debond after 30 days. Within 24 hr, half of the sample was thermocycled manually for 500 complete cycles between 5/55C and the remaining sample was stored in distilled water at room temperature and water was changed daily until debond time for each group was performed. The adhesive remnant index was tested under 20X magnification lens using stereomicroscope. Results and Conclusions: Both bracket types demonstrated high shear bond strength values before thermocycling (P?0.05), whereas after 500 thermocycles, there were significant changes in shear bond strength resulted in marked reduction in the stainless steel brackets than in the sapphire brackets (P?0.05). Shear bond strength values increased with time for both stainless steel and sapphire brackets with and without thermocycling (P?0.05). The tendency of bond failure was increased at the bracket/adhesive interface rather than enamel/bracket interface in the stainless steel brackets whereas at the enamel/bracket interface rather than bracket/adhesive interface in the sapphire brackets.